THE ROLE OF HIGH-PERFORMANCE SYSTEMS IN THE APPLICATION OF AGILE MANAGEMENT - Layla Mansour Mazhar (Scholars Digest Publishing, 2023)
This study aimed to clarify the role of high-performance systems in the application of agile management in Iraqi universities from the point of view of faculty members and to achieve the objectives of the study, the descriptive approach was used by preparing a questionnaire consisting of 25 items divided into five axes to clarify the role of high-performance systems in the application of agile management. The study sample consisted of 135 faculty members randomly selected from Iraqi universities, and the results showed that the role of high-performance systems in the application of agile management in all Iraqi universities came on average and came first in the field of problem solving, with a medium degree, while the field of changeability came to last place. The results showed moderately no differences in the role of high-performance systems in the application of agile management in Iraqi universities from the point of view of faculty members based on the variables of academic rank and practical experience.
Keywords: lean management, performance systems, Iraqi universities.